2005
DOI: 10.1016/j.femsle.2005.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence based assay ofGALsystem in yeastSaccharomyces cerevisiae

Abstract: The GAL1 promoter is one of the strongest inducible promoters in the yeast Saccharomyces cerevisiae. In order to improve recombinant protein production we have developed a fluorescence based method for screening and evaluating the contribution of various gene deletions to protein expression from the GAL1 promoter. The level of protein synthesis was determined in 28 selected mutant strains simultaneously, by direct measurement of fluorescence in living cells using a microplate reader. The highest, 2.4-fold incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 24 publications
1
9
1
Order By: Relevance
“…The amount and the specific productivity of the enzyme produced in the Dgal1 mutant were considerably lower compared with the wild type and Dgal80 strains. This is in contrast to the recent report [7] in which Dgal1 strain was superior to the Dgal80 strain in the expression level of GFP by GAL1 promoter. This discrepancy may be due in part to the fact that cultivation time of 24 h employed in their experiment was not long enough for expression of GAL1 promoter for which full derepression is effected only after complete exhaustion of glucose (see the following section).…”
Section: Straincontrasting
confidence: 99%
See 1 more Smart Citation
“…The amount and the specific productivity of the enzyme produced in the Dgal1 mutant were considerably lower compared with the wild type and Dgal80 strains. This is in contrast to the recent report [7] in which Dgal1 strain was superior to the Dgal80 strain in the expression level of GFP by GAL1 promoter. This discrepancy may be due in part to the fact that cultivation time of 24 h employed in their experiment was not long enough for expression of GAL1 promoter for which full derepression is effected only after complete exhaustion of glucose (see the following section).…”
Section: Straincontrasting
confidence: 99%
“…The Dgal1 mutant strain lacks galactokinase, and so cannot utilize galactose; high level of protein expression is evident even at low galactose concentrations. A recent fluorescence-based study of the GAL system using green fluorescence protein (GFP) screened and evaluated the contribution of 28 selected gene deletions to protein expression from the GAL1 promoter [7].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in the Gal1p knockout strain the inducer was also not consumed, but the level of GAL genes induction was significantly higher compared to induction in strains with impaired kinase function. Previously, it has been demonstrated that GAL genes expression is higher in gal1 deletion strain, presumably due to maintaining constant galactose concentration (Hovland et al 1989;Napp and Da Silva 1994;Kim et al 2004;Kang et al 2005;Š tagoj et al 2005). Data from this study clearly indicated that depletion of inducer is not the main limiting factor in GAL genetic switch.…”
Section: Discussionsupporting
confidence: 54%
“…Prior studies have demonstrated higher induction level of GAL genetic response in Gal1p null strain (Hovland et al 1989;Napp and Da Silva 1994;Š tagoj et al 2005). It was shown that maintaining constant level of inducer gives a significant higher expression of recombinant genes driven by a galactose-inducible promoters (Kim et al 2004;Kang et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation